Health education and renal optimization for empowered self-care H.E.R.O.E.S. - Ibrahim, Norkasihan (Faculty of Pharmacy, 2025)
The H.E.R.O.E.S. program was successfully conducted at the Orion Consortium Dialysis Centre in Masjid Tanah, Melaka, on 23–24 May 2025. This initiative was a collaborative effort between UITM’s three faculties Pharmacy, Health Sciences, and Medicinein partnership with Orion Consortium Dialysis Centre Sdn. Bhd. (OCSB), a national healthcare company specialising in dialysis services. The program was funded by OCSB under a 12-month community grant aimed at enhancing patients’ knowledge and confidence in managing their medications and renal diets through culturally sensitive, interactive learning sessions.